Glucagon-like peptide I and glucose-dependent insulinotropic polypeptide stimulate Ca2+-induced secretion in rat alpha-cells by a protein kinase A-mediated mechanism. - Ding, W; Renström, E; Rorsman, P; Buschard, K; Gromada, J (1997)
High-resolution capacitance measurements were used to explore the effects of the gut hormones GLP-I(7-36) amide [glucagon-like peptide I(7-36) amide] and GIP (glucose-dependent insulinotropic polypeptide) on Ca2+-dependent exocytosis in glucagon-secreting rat pancreatic alpha-cells. Both peptides produced a greater than threefold potentiation of secretion evoked by voltage-clamp depolarizations, an effect that was associated with an approximately 35% increase of the Ca2+ current. The stimulatory actions of GLP-I(7-36) amide and GIP were mimicked by forskolin and antagonized by the protein kinase A (PKA)-inhibitor Rp-8-Br-cAMPS. The islet hormone somatostatin inhibited the stimulatory action of GLP-I(7-36) amide and GIP via a cyclic AMP-independent mechanism, whereas insulin had no effect on exocytosis. These data suggest that the alpha-cells are equipped with receptors for GLP-I and GIP and that these peptides, in addition to their well-established insulinotropic capacity, also stimulate glucagon secretion. We propose that the reported inhibitory action of GLP-I on glucagon secretion is accounted for by a paracrine mechanism (e.g., mediated by stimulated release of somatostatin that in turn suppresses exocytosis in the alpha-cell).